2004
DOI: 10.1016/j.cbpb.2003.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the sponge Hymeniacidon sanguinea from the Canary Islands

Abstract: The fatty acid composition of the lipids from the sponge Hymeniacidon sanguinea was investigated and 73 acids were identified. Three of them were new and their structures, elucidated by gas chromatographyymass spectrometry, were identified as 13-methyl-icosanoic, 15-methyl-docosanoic and 3,13-dimethyl-tetradecanoic. Only 12 sterols were present, with cholestanol predominating in the volatile fraction; 22 compounds were identified, mainly hydrocarbons and fatty acids. In the n-butanol fraction, we found mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 21 publications
1
34
0
3
Order By: Relevance
“…Furthermore, although macroalgae constitute the main feeding resource of P. lividus, this sea urchin is an opportunistic species that can exploit other food resources such as microalgae, sponges, hydrozoa or copepods (Boudouresque and Verlaque 2007) whose occurrence could also diVer between both locations. For example, the source of 20:1n-11 found in higher proportions in the gonads of the specimens collected at La Herradura, could be sponges (Nechev et al 2004;Zimmerman et al 1989), that are more abundant at the rocky subtidal areas of La Herradura than at the swallow ponds of Torregorda. And the source of 20:1n-9 could be copepods which it is known to be enriched in this longchain monounsaturated fatty acid (Falk-Petersen et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although macroalgae constitute the main feeding resource of P. lividus, this sea urchin is an opportunistic species that can exploit other food resources such as microalgae, sponges, hydrozoa or copepods (Boudouresque and Verlaque 2007) whose occurrence could also diVer between both locations. For example, the source of 20:1n-11 found in higher proportions in the gonads of the specimens collected at La Herradura, could be sponges (Nechev et al 2004;Zimmerman et al 1989), that are more abundant at the rocky subtidal areas of La Herradura than at the swallow ponds of Torregorda. And the source of 20:1n-9 could be copepods which it is known to be enriched in this longchain monounsaturated fatty acid (Falk-Petersen et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Antifouling mechanisms affecting the early stages of organisms may differ from those involved in macroinvertebrate settlement. Latitudinal differences can also alter the chemical composition of organisms, as has been suggested for the sponge Aplysina fulva collected on the Brazilian coast (NUÑEZ et al, 2008). Further chemical studies arenecessary to corroborate this conclusion.…”
mentioning
confidence: 68%
“…Several compounds have already been reported for the genus Hymeniacidon, such as peptides, alkaloids, lipids and steroids (INABA et al, 1998;GRANATO et al, 2000;NECHEV et al, 2004;BLUNT et al, 2009), but little is known about their ecological roles. Previous studies have shown that L-5-hydroxytryptophan isolated from H. heliophila acts as a protection against UV radiation (LYSEK et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these FAs are common in nature and have been reported in sponges previously (Barnathan et al, 1996;Carballeira & Alicea, 2000;Carballeira & Lopez, 1989;Christie et al, 1992;Nechev et al, 2004). Palmitic acid is a precursor with chain elongation, desaturation and addition of side chain modifications possible (Michal & Schomburg, 2013).…”
Section: Fatty Acid and Sterol Compositionmentioning
confidence: 99%